E-commerce Transformation in Indonesia: Innovation and Creative Destruction - Dewi, Galuh Dian Prama; Lusikooy, Alvin Ernesto (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2023)
This study investigates the interplay between entrepreneurial dynamism, innovation, and technological advancement in Indonesia's burgeoning e-commerce sector. Framed through the lenses of Creative Destruction and Disruptive Innovation, the research delves into the transformative impact of digital globalization on traditional business models. By tracing the historical development of e-commerce and scrutinizing the closure of offline stores in 2017, this study highlights the potential of digital globalization to disrupt established market players, paving the way for MSMEs to explore unconstrained market segments. The study introduces the Model of Disruption-Destruction Cycle, elucidating how entrepreneurs' innovations lead to technological advancements and business model transformations. These dynamics enrich our understanding of Indonesia's evolving digital economy. The contribution lies in its comprehensive analysis of the transformative forces redefining the e-commerce landscape. While the study presents valuable insights, it also acknowledges limitations, including the need for further empirical validation. Finally, this paper offers a platform for empirically validating and exploring the ever-evolving landscape of entrepreneurship, innovation, and technological advancement in Indonesia's e-commerce realm.